Апеляційне провадження в цивільному процесі України - Іліопол, Інна Михайлівна; Илиопол, Инна Михайловна; Iliopol, Inna. M. (My University, 2018)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.03 - цивільне право і цивільний процес; сімейне право; міжнародне приватне право. - Національний університет «Одеська юридична академія», Одеса, 2018. Дисертація є першим у вітчизняній науці цивільного процесуального права спеціальним комплексним дослідженням апеляційного провадження в цивільному процесі України в умовах судової реформи та євроінтеграційних процесів. У дисертації розглянуто розвиток доктринальних поглядів та законодавчого регулювання апеляції в цивільному процесі у Стародавньому Римі, країнах Західної Європи та в Україні. З’ясовано місце права на апеляційний перегляд справи серед основоположних конституційних засад правосуддя в умовах реформування судової системи України. Розмежовано та визначено поняття «апеляція», «апеляційний перегляд справи», «апеляційне оскарження», «апеляційне провадження», а також надано визначення поняттю «право на апеляційний перегляд справи». Охарактеризовано реалізацію принципів цивільного судочинства в апеляційному провадженні. Розглянуто передумови права на пред’явлення апеляційної скарги та умови його реалізації. Виявлено характерні ознаки апеляційного провадження, а також види апеляції. Охарактеризовано процесуальний порядок розгляду судом апеляційної інстанції справ в умовах оновленого цивільного процесуального законодавства України. З’ясовано межі розгляду справи судом апеляційної інстанції та проаналізовано повноваження суду апеляційної інстанції. Розглянуто порядок винесення (постановлення) судових актів апеляційним судом та їх проголошення. Сформульовано науково обґрунтовані пропозиції з удосконалення цивільного процесуального законодавства України в частині апеляційного провадження.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.03 - гражданское право и гражданский процесс; семейное право; международное частное право. - Национальный университет «Одесская юридическая академия», Одесса, 2018. Диссертация является первым в отечественной науке гражданского процессуального права специальным комплексным исследованием апелляционного производства в гражданском процессе Украины в условиях судебной реформы и евроинтеграционных процессов. В диссертации обозначены методологические основы диссертационного исследования и выбраны его основные направления. На основе проведенного исторического анализа развития апелляции выделены его основные этапы и дана их характеристика. В работе предложено рассматривать апелляционное производство как институт гражданского процессуального права и как стадию гражданского процесса. Установлено, что право на предъявление апелляционной жалобы зависит от наличия определенных предпосылок указанного права. Выявлены характерные признаки апелляционного производства с учетом изменений гражданского процессуального законодательства, рассмотрены виды апелляции и установлено, что порядок рассмотрения дел при полной и неполной апелляции имеет определенные отличия, которые рассмотрены сквозь призму выделения недостатков и преимуществ каждого из видов апелляции. Охарактеризованы процессуальные особенности рассмотрения дел судом апелляционной инстанции в условиях обновленного гражданского процессуального законодательства Украины. Сформулированы научно обоснованные предложения по совершенствованию гражданского процессуального законодательства Украины, регулирующего апелляционное производство.

Dissertation for the scientific degree of Candidate of Law in specialty 12.00.03 - Civil Law and Civil Proceedings; Family Law; International Private Law.- National University “Odessa Academy of Law”, Odessa, 2018. This dissertation is the first special comprehensive research of appeal proceedings in civil process of Ukraine under the conditions of the judicial reform and euro integration processes to be found in the domestic science of civil procedural law. The dissertation outlines the methodological foundation of the research and choses basic directions thereof. Key stages of the evolution of the institute of appeal procedure have been distinguished on the basis of the relevant historic analysis. The place of the right to appeal review of cases among other constitutional fundamentals of justice under the condition of Ukraine’s judicial system reform has been specified. Delimitation lines were drawn between and definitions were given to the notions “appeal”, “appeal review of a case”, “appeal challenge” and “appeal proceedings”; further, the notion of the “right to appeal review of cases” was defined. The work propounds to view appeal proceedings as an institute of civil procedural law and a stage of civil process. The institute of appeal proceedings has been considered taking into account the introduction of new principles in the civil proceedings of Ukraine, namely those of legal certainty, finality of the judgment, proportionality and inadmissibility of procedural rights abuse. It has been specified that the right to submission of an appeal depends upon the availability of certain prerequisites of the above mentioned right. The classification of these prerequisites has been propounded depending upon the characteristics of the case: 1) subjective prerequisites connected with the person (substantive legal, procedural interest (legal interest); the absence of a refusalto exercise the right to file an appealdeclared in accordance with the law; 2)objective prerequisites, depending on the subject matter, which is submitted for consideration by the court of appellate instance (judgments of the first instance as an object of appeal);the competence of the court to hear the case; the exclusion of this category from the cases to be considered in appeal proceedings; availability of a decision that has entered into legal force in the case between the same parties on the same subject and grounds. The characteristic features of appeal proceedings have been specified taking into account the amendments to the civil procedural law. The types of appeal have been examined and it was established that the procedure for dealing with cases with full and incomplete appeal has particular differences that were considered through the prism of highlighting the shortcomings and advantages of each type of appeal. The procedural features of consideration of cases by courts of appellate instance in the conditions of the updated civil procedural legislation have been characterized. The peculiarities of institution of the appellate proceedings have been investigated; the general characteristic of the possibility of filing an appeal in electronic form was given. The stages of the appellate proceedings have been singled out and a brief description of the preparation and procedure for consideration of casesby the court of appealhas been provided. The limits of the appeal court’s review as well as the powers of the appellate court have been analyzed through the prism of the latest novelties in the legislation. Scientifically grounded propositions concerning the improvement of civil procedural legislation of Ukraine dealing with appeal proceedings have been formulated.
дис. ... канд. юрид. наук: 12.00.03
Іліопол І.М. Апеляційне провадження в цивільному процесі України: дис. ... канд. юрид. наук: 12.00.03 / Іліопол Інна Михайлівна. - Одеса, 2018. - 250 с.
Keywords: апеляційне провадження; апеляція; апеляційний перегляд справ; апеляційне оскарження; апеляційна скарга; учасники справи; суд апеляційної інстанції; апелляционное производство; апелляция; апелляционный пересмотр дел; апелляционное обжалование; апелляционная жалоба; участники дела; суд апелляционной инстанции; appeal proceedings; appeal; appeal review of cases; appellate challenge; participants in a case; court of appeal instance